Double doping of V and F on Co3O4 nanoneedles as efficient electrocatalyst for oxygen evolution. (3rd June 2021) - Xie, Jing-Yi; Fan, Ruo-Yao; Fu, Jia-Yu; Zhen, Yi-Nuo; Li, Meng-Xuan; Liu, Hai-Jun; Ma, Yu; Wang, Fu-Li; Chai, Yong-Ming; Dong, Bin
Abstract: Rationally designing high-activity catalyst for oxygen evolution reaction (OER) is of primary importance due to its sluggish kinetic process in water splitting. Herein, we report a metallic (V) and nonmetallic (F) double doping in Co3 O4 with nanoneedles structure, which is synthesized through facile oil bath and annealing. Electrochemical measurements show that the Co3 O4 dopped with fluorine and vanadium (F0.2 -V-Co3 O4 -350) only needs a low overpotential of 320 mV to afford a current density of 10 mA cm −2, which is superior to commercial RuO2 . The excellent electrocatalytic performance can be attributed to double doping of vanadium and fluorine which have strong electron absorption effect to optimize the density of electrons in Co3 O4 . Besides, nanoneedles structure can enlarge exposure of active sites. And its great durability is evaluated through 2000 cycles CV test. Furthermore, the optimal ratio of fluorine to vanadium and different annealing temperatures of the target catalyst are explored reasonably. Graphical abstract: Image 1 Highlights: The double doping of V and F has strong effect on the density of electron in Co3 O4 . F0.2 -V-Co3 O4 -350 only needs an overpotential of 320 mV at 10 mA cm −2 . The optimal ratio of F to V and annealing temperature have been explored. The trace introduction of both metallic and nonmetallic can improve OER activity.